Comparison of Acoustic Radiation Force Impulse (ARFI) Elastography Measurements with the 4C1 Transducer to the 6C1HD Transducer: A Phantom and Patient Study - Pfeifer, Lukas; Görtz, Rüdiger; Neurath, Markus; Strobel, Deike; Wildner, Dane (Ultraschall in der Medizin, 2016)
Purpose: The aim of this study was to evaluate whether acoustic radiation force impulse (ARFI) elastography done with the 4C1 probe yields comparable results to the recently introduced 6C1HD probe. Materials and Methods: Measurements with the 4C1 and 6C1HD probes (Acuson S2000) were performed and compared in four different inclusions of an elasticity phantom model (QA049 CIRS) as well as in the liver of healthy individuals and patients with liver cirrhosis. Results: Measurements with the 6C1HD probe were slightly higher in all phantom inclusions (8, 14, 45, 80kPA) with a mean of 1.48 m/s (95 %-CI; 1.47 - 1.49), 2.18 m/s (95 %-CI; 2.17 - 2.19), 3.61 m/s (95 %-CI; 3.57 - 3.64) and 4.34 m/s (95 %-CI; 4.29 - 4.39) compared to the 4C1 transducer with 1.46 m/s (95 %-CI; 1.45 - 1.47), 2.15 m/s (95 %-CI; 2.14 - 2.16), 3.39 m/s (95 %-CI; 3.37 - 3.41) and 3.98 m/s (95 %-CI; 3.75 - 4.21), respectively (p = 0.04, p < 0.01, p < 0.01, p < 0.01). Cirrhotic patients (n = 40) had a higher mean shear wave speed with 3.00 m/s (95 %-CI; 2.80 - 3.21) with the 6C1HD transducer compared to 2.81 m/s (95 %-CI; 2.64 - 2.99) with the 4C1 transducer (p = 0.03). Healthy individuals (n = 20) had a mean shear wave speed of 1.12 m/s (95 %-CI; 1.06 - 1.17) with the 6C1HD probe and 1.12 m/s (95 %-CI; 1.05 - 1.19) with the 4C1 probe (p = 0.96). Conclusion: ARFI values assessed with a 6C1HD transducer are slightly higher than measurements with a 4C1 transducer in an ARFI phantom and in patients with liver cirrhosis. As the difference is small, current cut-off values keep their usefulness but should be interpreted with caution if measurements are close to the cut-off.
EVALuna2:2195